Electricity governance and the Western energy imbalance market in the United States: The necessity of interorganizational collaboration. (September 2016) - Lenhart, Stephanie; Nelson-Marsh, Natalie; Wilson, Elizabeth J.; Solan, David
Abstract: In the Western United States, widespread growth of wind and solar resources is putting pressure on state policy makers, electricity system operators, and utilities to integrate renewable resources into the grid, while maintaining reliability, affordability, and improving efficiency. These resources are creating new challenges because their variability can contribute to transmission constraints and system imbalances. This paper examines a recent initiative to make energy imbalance market services available throughout the Western Interconnection and provides insight into evolving electricity system governance. Drawing on boundary organization and interorganizational collaboration literature, this research explores the processes and practices used to create a new interorganizational collaboration. The research supports theoretical claims that facilitating policy innovation requires discursive formation of a collective identity.